2021
DOI: 10.1016/j.bmc.2021.116364
|View full text |Cite
|
Sign up to set email alerts
|

Potency and pharmacokinetics of GS-441524 derivatives against SARS-CoV-2

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…After administration of ATV006, it is rapidly hydrolyzed by cellular esterases to produce the parent nucleoside GS-441524 (55,56), which then undergoes three steps of phosphorylation and is transformed to the active triphosphate form, the same active component as that of remdesivir and GS-441524. Therefore, ATV006 and remdesivir have the same mechanism of stalling SARS-CoV-2 polymerase by targeting viral RdRp (45,(57)(58)(59). It is expected that ATV006 could be active against different variants of SARS-CoV-2, as the RdRp is the highly conserved amongst coronaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…After administration of ATV006, it is rapidly hydrolyzed by cellular esterases to produce the parent nucleoside GS-441524 (55,56), which then undergoes three steps of phosphorylation and is transformed to the active triphosphate form, the same active component as that of remdesivir and GS-441524. Therefore, ATV006 and remdesivir have the same mechanism of stalling SARS-CoV-2 polymerase by targeting viral RdRp (45,(57)(58)(59). It is expected that ATV006 could be active against different variants of SARS-CoV-2, as the RdRp is the highly conserved amongst coronaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of GS-441524 to GS-443902 was previously assumed to be rate limited, and therefore, the efficacy of remdesivir was considered a result of metabolism from remdesivir directly to GS-443902 ( 8 ). However, more evidence is emerging that GS-441524 is also effectively metabolized to GS-443902 in in vitro lung cell models and could also contribute to the antiviral effect of remdesivir ( 7 , 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“… 2 Thus, GS-441524 has the potential to be developed further as an orally available anti-viral drug. 3 A double-blind, randomized, placebo-controlled clinical trial of over 1000 patients from 60 countries showed that remdesivir was superior to placebo in shortening the rehabilitation time of hospitalized patients, while lowering the frequency of respiratory tract infections. 4 …”
Section: Introductionmentioning
confidence: 99%